Feasibility, acceptability and change in health following a telephone-based cognitive behaviour therapy intervention for patients with axial spondyloarthritis. Issue 2 (17th November 2020) - Pedley, Rebecca; Dean, Linda E; Choy, Ernest; Gaffney, Karl; Ijaz, Tanzeel; Kay, Lesley; Lovell, Karina; Molloy, Christine; Martin, Kathryn; Packham, Jonathan; Siebert, Stefan; Sengupta, Raj; et al.
Abstract: Objective: The aim was to assess the feasibility and acceptability of a telephone-based cognitive behaviour therapy (tCBT) intervention for individuals with axial SpA (axSpA), with and without co-morbid FM, and to measure the change in patient-reported health outcomes. Methods: A convenience sample of individuals recruited from British Society for Rheumatology Biologics Registry for AS (BSRBR-AS) sites were offered a course of tCBT (framed as coaching). Patient-reported outcomes were measured at baseline and on course completion. Semi-structured qualitative interviews assessed intervention acceptability. Thematic analysis was informed by the theoretical framework of acceptability. Results: Forty-two participants attended for initial assessment. Those completing at least one tCBT session ( n = 28) were younger, more likely to meet classification criteria for FM (57 vs 29%) and reported higher disease activity. Modest improvements were reported across a range of disease activity and wider health measures, with 62% of patients self-rating their health as improved (median 13 weeks post-intervention). Twenty-six participants were interviewed (including six who discontinued after initial assessment). tCBT was widely acceptable, offering a personalized approach. Despite low or unclear expectations, participants described improved sleep and psychological well-being and gained new skills to support self-management. Reasons for non-uptake of tCBT centred on lack of perceived need and fit with individual value systems. Many felt that tCBT would be most useful closer to diagnosis. Conclusion: Higher uptake among axSpA patients with co-morbid FM suggests that these individuals have additional needs. The findings are helpful in identifying patients most likely to engage with and benefit from tCBT and to maximize participation.